An Investigation Of Best Practice On Students' Mathematical Communication Using Presentation Boards - Sasongko, Luddy Bambang; Lefrida, Rita (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
Tulisan ini merupakan best practice yang dilakukan di SMA Model Madani Palu. Sebelumnya alur pembelajaran yang dilakukan yaitu mengerjakan tugas dibuku, menuliskan di papan tulis dan  dan mempresentasikan dengan membacakan hasilnya. Kemudian ditemukan media papan presentasi yang sederhana dan inovatif. Selain itu biaya untuk membuat papan presentasi relative murah. Media ini dapat dipergunakan berulang-ulang karena ditulis dengan spidol dan dapat dihapus.  Metode yang dilakukan, siswa menuliskan pekerjaannya pada papan presentasi. Penggunaan media ini dapat menggali komunikasi matematis siswa, karena siswa terlatih menyampaikan dan menuliskan langsung hasil yang diperoleh. Hal ini diperkuat berdasarkan hasil pengisian angket bahwa penggunaan papan presentasi (1) dapat memotivasi siswa sehingga terlibat dalam menjawab soal atau selama kegiatan pembelajaran di kelas, (2) memberanikan diri tampil kerja/tugas yang diberikan di kelas, (3) merasa tertantang untuk mengerjakan tugas matematika yang diberikan karena kolaborasi (4) Menyelesaikan tugas-tugas dalam pembelajaran ini membuat siswa merasa puas terhadap hasil yang mereka capai, (5) Siswa terlibat aktif dalam kelompok, (6) berani menyampaikan ide gagasan secara tertulis dan lisan dan(7)  melakukan suatu hal lebih detailsi.   This study aims to investigate the best practice of mathematical communication carried out at SMA Model Madani Palu. In mathematical communication, the learning flow was conducted by doing assignments in books, writing on the board, and presenting the results through reading. Then, a media in the form of presentation board which is simple and innovative was found. In addition, the cost of making a presentation board is relatively cheap. This media can be used repeatedly because it is written with erasable markers. The method used, students write their work on the presentation board The use of this media is expected to be able to explore students' mathematical communication as they are trained to convey and write down the results obtained directly on it. This statement is reinforced by the results of the questionnaire that was disseminated in this study. From this study, it was found that the use of a presentation board (1) can motivate students to be involved in answering questions or during learning activities in class, (2) make students to be braver to perform work/assignments given in class, (3) challenge students to work on the given collaborative mathematical assignments, (4) make students feel satisfied by completing the assignments, (5) involve students in a group, (6) make students dare to convey ideas in writing or orally, and (7) encourage students to do something more detailed.